Incidental identification of neonatal babesiosis: a case report - Samiksha Tarun; Ian A. Mellis; Abdullah Kilic; Daniel A. Green; Makoto Tokiwa; Gregory J. Berry; Fann Wu; Shivang S. Shah (BMC Pediatrics)
Abstract Background Evaluation of suspected neonatal sepsis rarely considers diagnostic workup for vector-borne illnesses, as these are generally infrequent etiologies in the febrile neonate. Babesiosis -- a zoonosis caused by apicomplexan parasites of the genus Babesia and spread to humans by the Ixodes scapularis tick -- can either be clinically silent, or symptomatic with fever, constitutional symptoms, as well as anemia and thrombocytopenia. We report here a rare case of neonatal babesiosis that was incidentally identified during routine workup for neonatal sepsis. Case presentation A full-term male neonate with fever was admitted to the hospital for sepsis evaluation. On routine complete blood count with manual differential blood smear, parasites were incidentally detected, later identified as Babesia microti. On review of maternal history, there was antenatal history of unexplained thrombocytopenia and anemia, and post-hoc review of peripartum maternal blood smear showed rare intra-erythrocytic parasites, which were confirmed as B. microti by PCR testing of maternal blood. Ultimately, the infant was successfully treated with azithromycin and atovaquone, received a red blood cell transfusion for symptomatic anemia, and remained well at his outpatient follow-up visit. Conclusion This unusual case highlights the importance of including neonatal babesiosis in the differential diagnosis for neonatal sepsis in endemic regions, including careful review of maternal antenatal exposure history and labs, and consideration of peripheral blood smear in suggestive cases.